Thioxanthylium Cations: Highly Reversible Hydrochromic Mate‐rials with Tunable Color and Moisture Sensitivity. Issue 65 (20th September 2022) - Chua, Ming Hui; Soo, Xiang Yun Debbie; Goh, Wei Peng; Png, Zhuang Mao; Zhu, Qiang; Xu, Jianwei
Abstract: Hydrochromic materials, which change color in response to moisture, are highly sought‐after due to some unique applications such as moisture detection, humidity monitoring, anti‐counterfeiting, and sweat‐pore mapping. We herein report a new thioxanthene‐9‐ols/thioxanthylium cations hydrochromic system. The hydrochromic thioxanthylium cations can be generated/regenerated by exposing a chemically stable thioxanthene‐9‐ol to trifluoroacetic acid (TFA). The intensely colored thioxanthylium cations can be chemically reverted to the colorless thioxanthene‐9‐ol. Interestingly, the conversion between thioxanthene‐9‐ol and its cation species was found to be highly reversible in most cases (up to 50 activation‐deactivation cycles). The color and moisture‐sensitivity of thioxanthylium cations were also validated to be tunable via functionalization of the thioxanthene core with different aliphatic and aromatic groups at its 9 or 2, 7‐positions. Finally, paper probes were prepared using solution‐immersion and inkjet‐printing techniques to demonstrate the system's potential applications in humidity sensing and anti‐counterfeiting Abstract : Hydrochromism of thioxanthylium cations/ thioxanthene‐9‐ol can be tuned by structural functionalization to offer diverse colors and moisture‐sensitivities. This reversible hydrochromic system is easily activated with organic acid from chemically stable precursors, allowing for possible uses in moisture‐sensing and anti‐counterfeiting encryption.